CaM kinase II regulates cardiac hemoglobin expression through histone phosphorylation upon sympathetic activation - Saadatmand, Ali R.; Sramek, Viviana; Finke, Daniel; Dewenter, Matthias; Sticht, Carsten; Gretz, Norbert; Wüstemann, Till; Hagenmüller, Marco; Lehmann, Lorenz; Backs, Johannes (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Sympathetic activation of β-adrenoreceptors (β-AR) represents a hallmark in the development of heart failure (HF). However, little is known about the underlying mechanisms of gene regulation. In human ventricular myocardium from patients with end-stage HF, we found high levels of phosphorylated histone 3 at serine-28 (H3S28p). H3S28p was increased by inhibition of the catecholamine-sensitive protein phosphatase 1 and decreased by β-blocker pretreatment. By a series of in vitro and in vivo experiments, we show that the β-AR downstream protein kinase CaM kinase II (CaMKII) directly binds and phosphorylates H3S28. Whereas, in CaMKII-deficient myocytes, acute catecholaminergic stimulation resulted in some degree of H3S28p, sustained catecholaminergic stimulation almost entirely failed to induce H3S28p. Genome-wide analysis of CaMKII-mediated H3S28p in response to chronic β-AR stress by chromatin immunoprecipitation followed by massive genomic sequencing led to the identification of CaMKII-dependent H3S28p target genes. Forty percent of differentially H3S28p-enriched genomic regions were associated with differential, mostly increased expression of the nearest genes, pointing to CaMKII-dependent H3S28p as an activating histone mark. Remarkably, the adult hemoglobin genes showed an H3S28p enrichment close to their transcriptional start or end sites, which was associated with increased messenger RNA and protein expression. In summary, we demonstrate that chronic β-AR activation leads to CaMKII-mediated H3S28p in cardiomyocytes. Thus, H3S28p-dependent changes may play an unexpected role for cardiac hemoglobin regulation in the context of sympathetic activation. These data also imply that CaMKII may be a yet unrecognized stress-responsive regulator of hematopoesis.
Gesehen am 11.12.2019